2002
DOI: 10.1128/aac.46.9.2811-2820.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Amino Acid Mutations in Porin IB That Mediate Intermediate-Level Resistance to Penicillin and Tetracycline in Neisseria gonorrhoeae

Abstract: PenB is the third resistance determinant in the stepwise acquisition of multiple resistance genes in chromosomally mediated resistant Neisseria gonorrhoeae (CMRNG). Alterations in por IB , one of two alleles at the por locus that encodes the outer membrane protein porin IB (PIB), were recently reported to be responsible for the increased resistance to penicillin and tetracycline conferred by penB, but the specific mutations conferring antibiotic resistance were not identified experimentally. To determine which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 45 publications
4
142
0
1
Order By: Relevance
“…Nonselective substrate translocation pathways are challenging to identify by x-ray crystallography because the solutes are unlikely to make specific interactions with the channel. However, the location of bound heavy atoms in the derivative datasets and previous studies of antibiotic resistance mutations (15,16) hint at the location of a cation-selective pathway in PorB. The Lu 3þ and Er 3þ derivative datasets (SI Text and Table S2) identify an electronegative location approaching the pore funnel where cations may be attracted prior to translocation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonselective substrate translocation pathways are challenging to identify by x-ray crystallography because the solutes are unlikely to make specific interactions with the channel. However, the location of bound heavy atoms in the derivative datasets and previous studies of antibiotic resistance mutations (15,16) hint at the location of a cation-selective pathway in PorB. The Lu 3þ and Er 3þ derivative datasets (SI Text and Table S2) identify an electronegative location approaching the pore funnel where cations may be attracted prior to translocation.…”
Section: Resultsmentioning
confidence: 99%
“…In N. gonorrhoeae, the PenB antibiotic resistance mutations map to the PorB (15,16). In conjunction with mutations in the PorA porin and the MtrR transcription factor, these PenB mutations confer intermediate resistance to penicillin and tetracycline.…”
mentioning
confidence: 99%
“…sequence analyses of the por gene have identified aminoacid substitutions (G120D, a121D and G121K) in the putative internal loop 3 in various resistant strains 54,55 . Other mutations at these positions have been identified in resistant clinical isolates from a separate study, emphasizing the importance of these residues in the penicillinresistant phenotype 54,56 . substitution of these amino-acid residues using targeted mutagenesis has clearly shown that they have a role in antibiotic diffusion 55,57 .…”
Section: Nature Reviews | Microbiologymentioning
confidence: 99%
“…For instance, a G-to-D mutation in loop 3 of the OmpF/OmpC-like protein of Enterobacter aerogenes leads to a loss of conductance of the pore and, as a result, to decreased susceptibility to ␤-lactams (48). Similarly, mutations in loop 3 of the porin PIB of Neisseria gonorrhoeae confer resistance to penicillin and tetracycline in strains that simultaneously overexpress an efflux pump due to an mtrR mutation (189,190). In Vibrio cholerae, a D116A mutation in OmpU, which was predicted to be an antibiotic binding site, leads to increased resistance to cephalosporins (193).…”
Section: Resistance Due To Mutations In Porin-encoding Genesmentioning
confidence: 99%